POTENSI REDUKSI LIMPASAN PERMUKAAN DENGAN METODE SOIL CONSERVATION SERVICE - CURVE NUMBER DI KELURAHAN RAWA BUNTU - Steffany Trifena; Dwi Prabowo (Indonesian Journal of Spatial Planning, 2020)
Development in Rawa Buntu Subdistrict caused land use change and made green space  area  in  Rawa  Buntu  Subdistrict  decreased,  so  it  could  cause  flood.  This research  was  conducted  to  know  the  potential  of  rainwater  runoff  reduction  in each type of land cover in Rawa Buntu Subdistrict to serve as the basis for better planning in the future. The Soil Conservation Service - Curve Number (SCS-CN) method  is  used  to  calculate  the  total  rainfall  runoff  that  can  be  reduced  and  to know  the  role  of  green  space  in  reducing  rainwater  runoff.  The  result  of  the research shows that residential area dominates Rawa Buntu Subdistrict about 65% and  green  space  is  only  about  18%.  The  volume  of  rainfall  runoff  that  can  be reduced  each  month  on  AMC  I,  AMC  II  and  AMC  III  is  74,4MGal,  37,8MGal and  17,9MGal  with  green  space  contribution  of  27%,  31,2%  and  36,4%  of  the total rainfall runoff that can be reduced for each AMC condition.